“A pré-escola não é uma preparação para o ensino fundamental”: a identidade de pré-escolas de Fortaleza sob a ótica de professoras de educação infantil - Ramos, Bruna Brito (2022)
This research sought to study the identity of preschools in the municipal public of the city of Fortaleza (CE), from the perspective of early childhood education (ECE) teachers, after the mandatory enrollment of children from the age of 4. A theoretical framework was built that involved issues relevant to the concept of identity, notably, institutional, in the light of studies by Etzioni (1989), Hatch and Schultz (1997) and Fernandes (2014). As main source consulted the writings of Kuhlmann Jr. (1991; 1998; 2000), a history of Brazilian ECE was made, with emphasis on the political, economic and pedagogical factors involved therein, in order to identify some of the discourses that permeate the construction of the identity of preschool, here as a “social unity”. The main source for the generation of data from the qualitative research developed was the semi-structured interview, carried out through video-call with 4 preschool teachers from the municipal public education of Fortaleza. To register the interviews, video calls were recorded, in addition to written records. The data resulting from this procedure were analyzed, inspired by the content analysis of Bardin (1977), in line with the research objectives and the theoretical adopted. Therefore, based on the constructed data, thematic axes were listed such as: perception/purpose of early childhood and preschool education; environments; physical structure; activities and learning, which were linked to the categories: preschool objective; aspects that distinguish preschool from elementary school- early years; and pedagogical practices, respectively. The data pointed to an understanding that teachers participating in the research have been seeking to put into practice what is stated in official documents (BRASIL, 2009c), such as promoting the integral development of children through interactions and games, however, there are barriers that make it difficult this process, such as the influences of schooling conceptions predominant in elementary school - early years, which subjugate the actions, space, time and material of preschools, something that becomes even more latent when there are two distinct stages of basic education. in the same geographic space. As influences of elementary school - early years - in preschool, without a doubt, make it difficult to perceive what this sub-stage of early childhood education is, so there is a need for attention, care and reflection, mainly on the part of the education coordinator of the SME, in order to explain in programs and practices, what type of preschool is intended for children from 4 to 5 years old.